2021
DOI: 10.1002/bab.2112
|View full text |Cite
|
Sign up to set email alerts
|

Role of neddylation in neurological development and diseases

Abstract: Neddylation, a posttranslational protein modification, refers to the specific conjugation of NEDD8 to substrates, which is of great significance to various biological processes. Besides members of the cullin protein family, other key proteins can act as a substrate for neddylation modification, which remarkably influences neurodevelopment and neurodegenerative diseases. Normal levels of protein neddylation contribute to nerve growth, synapse strength, neurotransmission, and synaptic plasticity, whereas overact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 108 publications
0
11
0
Order By: Relevance
“…CUL3 normally undergoes covalent modification by addition (catalyzed by NEDD8-activating enzyme) and then removal (catalyzed by c-Jun activation domain-binding protein-1, JAB1), of the 9KDa ubiquitin-like protein NEDD8. This cycling of NEDD8 addition/removal (“neddylation”/“deneddylation”) is essential for the stability and activity of the CRL, and has been shown to be physiologically important in multiple organs including the heart, 11 the brain, 12 and the immune system 13 . In the kidney, recent evidence from studies in mice suggests that cullin neddylation status changes in response to dietary potassium, 6 or in models of diabetes 14 , 15 .…”
mentioning
confidence: 99%
“…CUL3 normally undergoes covalent modification by addition (catalyzed by NEDD8-activating enzyme) and then removal (catalyzed by c-Jun activation domain-binding protein-1, JAB1), of the 9KDa ubiquitin-like protein NEDD8. This cycling of NEDD8 addition/removal (“neddylation”/“deneddylation”) is essential for the stability and activity of the CRL, and has been shown to be physiologically important in multiple organs including the heart, 11 the brain, 12 and the immune system 13 . In the kidney, recent evidence from studies in mice suggests that cullin neddylation status changes in response to dietary potassium, 6 or in models of diabetes 14 , 15 .…”
mentioning
confidence: 99%
“…However, to date, the relevance of hnRNPA2B1 as a potential therapeutic target has not been tested in clinical trials. In contrast, several clinical trials examining the therapeutic potential of neddylation inhibitors against cancer [ 42 , 43 ], as well as in neurological diseases [ 44 ] are in progress. Future studies will help determine whether neddylation inhibitors may be a beneficial therapeutic approach for HTGP, potentially through the regulation of hnRNPA2B1.…”
Section: Discussionmentioning
confidence: 99%
“…In a work by Jegga et al [ 67 ], via a systems biology approach a significant number of genes have been identified for their involvement of ALP, from which 23 are currently highlighted in our own results ( HDAC6 , MTOR , NFKB1 , ITPR1 , TSC1 , LRP2 , PRKCD , SORT1 , ESR1 , MAPK8 , MYC , DAPK1 , TP63 , MAPK1 , NRG1 , ERN1 , FOXO3 , ITGB1 , ATG5 , AKT1 , RPS6KB1 , BECN1 , BCL2L1 ). Furthermore, synaptic plasticity and excitatory transmission are regulated by neuronal neddylation, which contributes to nerve growth, synapse strength, neurotransmission, and synaptic plasticity at normal levels, but the overactivation of protein neddylation pathways leads to apoptosis, neuronal autophagy, and tumor growth [ 68 ]. This knowledge enhances our findings that neddylation related genes are highly correlated to memory function in AD.…”
Section: Discussionmentioning
confidence: 99%